2015
DOI: 10.1111/joim.12454
|View full text |Cite
|
Sign up to set email alerts
|

Gene variance in the nicotinic receptor cluster (CHRNA5‐CHRNA3‐CHRNB4) predicts death from cardiopulmonary disease and cancer in smokers

Abstract: BackgroundGenetic variation in the cluster on chromosome 15, encoding the nicotinic acetylcholine receptor subunits (CHRNA5‐CHRNA3‐CHRNB4), has shown strong associations with tobacco consumption and an additional risk increase in smoking‐related diseases such as chronic obstructive pulmonary disease (COPD), peripheral artery disease and lung cancer.ObjectivesTo test whether rs1051730 (C/T), a tag for multiple variants in the CHRNA5‐CHRNA3‐CHRNB3 cluster, is associated with a change in risk of smoking‐related m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…The role of nAChRs has been intensely studied in the growth, angiogenesis and metastasis of lung cancer . The reason for this trend is due to GWAS studies showing genetic variations in α5‐α3‐β4 nAChR cluster (CHRNA5‐CHRNA3‐CHRNB4) associated with increased risk of death from lung cancer, COPD and tobacco‐related cancers . Conventionally, the α7‐nAChR is thought to mediate the proliferative, pro‐angiogenic and pro‐metastatic activity of nicotine in lung cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of nAChRs has been intensely studied in the growth, angiogenesis and metastasis of lung cancer . The reason for this trend is due to GWAS studies showing genetic variations in α5‐α3‐β4 nAChR cluster (CHRNA5‐CHRNA3‐CHRNB4) associated with increased risk of death from lung cancer, COPD and tobacco‐related cancers . Conventionally, the α7‐nAChR is thought to mediate the proliferative, pro‐angiogenic and pro‐metastatic activity of nicotine in lung cancer .…”
Section: Discussionmentioning
confidence: 99%
“…13,30 The reason for this trend is due to GWAS studies showing genetic variations in α5-α3-β4 nAChR cluster (CHRNA5-CHRNA3-CHRNB4) associated with increased risk of death from lung cancer, COPD and tobacco-related cancers. 14,31 Conventionally, the α7-nAChR is thought to mediate the proliferative, pro-angiogenic and pro-metastatic activity of nicotine in lung cancer. 32 Other genomic variances near CHRNA2 gene were correlated to increased overall risk for developing lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, these variants account for only 1%–2% of all COPD cases [5]. Genetic variations in the cluster on chromosome 15, encoding the nicotinic acetylcholine receptor subunits (CHRNA5-CHRNA3-CHRNB4), are correlated with tobacco addiction and increased risk of COPD, peripheral artery disease, lung cancer and obesity [6,7,8]. Different studies on lung tissue and peripheral blood identified increased expression of genes related to inflammatory pathways and immune regulation [9].…”
Section: Introductionmentioning
confidence: 99%
“…As both drinking and smoking behaviors are strongly associated with numerous health consequences, many studies have sought to link genes implicated in risk for smoking and drinking behaviors to the adverse health consequences of these behaviors, obtaining consistent results (Druesne-Pecollo et al, 2009;Li et al, 2011Li et al, , 2012Chen et al, 2015;Hallden et al, 2015). However, owing to the potent effects that nicotine, alcohol, and their metabolites have on the human body (Guo and Ren, 2010;Drug Therapeutics Bulletin, 2014), smoking and drinking behaviors and their associated genes (with large effects on nicotine response and acetaldehyde metabolism, respectively) might be involved in a much wider range of health conditions and human behaviors than is currently recognized.…”
Section: Introductionmentioning
confidence: 99%